Machine translation: A threat or an opportunity for human translators? - Puchała-Ladzińska, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The motivation behind any kind of development is always the wish to make a certain area of life easier. Hence, it is not surprising that attempts have been made to eliminate the barrier which has been a nuisance for people since time immemorial – the language barrier. Nowadays linguists and computer scientists worldwide strive to create miniature computers that could serve as universal translators, capable of translating between any two languages. This idea, once belonging to the realm of dreams only, is something that Google, among others, intends to turn into a reality. The purpose of the article is to explain the idea of machine translation (MT), present a brief outline of its history, evaluate the progress that has been made in this field of translation studies, as well as discuss the future of machine translation and try to answer the question whether it is likely that human translators will one day be replaced with artificial intelligence.
Keywords: machine translation (MT); Natural Language Processing (NLP); hypothesis of strong artificial intelligence